Shaping the Disciplined Character of Students in Islamic Madrasah Diniyah - Mukhlas, Misbakul Munir, Ifrohan (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study aims to describe the character of student discipline at Madrasah Diniyah Nurul Yaqien Pohlandak. The study was conducted using a descriptive qualitative approach with a case study design. Data collection techniques used observation, in-depth interviews, and documentation studies. Data credibility checking was carried out using triangulation techniques (sources and techniques/methods), member checks, and the adequacy of reference materials. The results of the study indicate that the character of student discipline at Madrasah Diniyah Nurul Yaqien Pohlandak, namely through: a) Discipline in performing prayers on time b) Orderly in ablution. c) Discipline in placing rows. d) Dhikr and prayer after performing congregational prayers